1996
DOI: 10.1037/0022-3514.70.2.336
|View full text |Cite
|
Sign up to set email alerts
|

Postbereavement depressive mood and its prebereavement predictors in HIV+ and HIV– gay men.

Abstract: Prebereavement predictors of the course of postbereavement depressive mood were examined in 110 gay men who were their partner's caregiver until the partner's death of AIDS. In all, 37 HIV+ and 73 HIV- bereaved caregiving partners were assessed bimonthly throughout a 10-month period beginning 3 months before and ending 7 months after the partner's death. Throughout the 10 months, mean Centers for Epidemiology Scale-Depression (CES-D) scores on depressive mood were above the cutoff for being at risk for major d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 55 publications
5
94
0
5
Order By: Relevance
“…Other studies have found that certain coping behaviors are associated with lower levels of depressive symptoms among HIV + individuals both cross-sectionally (Commerford, Gular, Orr, Resniko & O'Dowd, 1994;Fleishman & Fogel, 1994;Fukunishi et al, 1997;Leserman, Perkins & Evans, 1992) and prospectively (Fleishman & Fogel, 1994;Vedhara & Nott, 1996). Although stress moderation has not been directly tested, several studies have found that various coping styles are associated with less severe depressive reactions during acute stressors such as natural disasters (Benight et al, 1997), bereavement (Folkman, Chesney, Collette, Boccellari & Cooke, 1996), and seropositivity noti®-cation (Lutgendorf et al, 1997). However, there is also evidence that stress can adversely aect coping behaviors among HIV + individuals (Folkman, Chesney, Pollack & Coates, 1993) raising the possibility of bidirectional in¯uences.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that certain coping behaviors are associated with lower levels of depressive symptoms among HIV + individuals both cross-sectionally (Commerford, Gular, Orr, Resniko & O'Dowd, 1994;Fleishman & Fogel, 1994;Fukunishi et al, 1997;Leserman, Perkins & Evans, 1992) and prospectively (Fleishman & Fogel, 1994;Vedhara & Nott, 1996). Although stress moderation has not been directly tested, several studies have found that various coping styles are associated with less severe depressive reactions during acute stressors such as natural disasters (Benight et al, 1997), bereavement (Folkman, Chesney, Collette, Boccellari & Cooke, 1996), and seropositivity noti®-cation (Lutgendorf et al, 1997). However, there is also evidence that stress can adversely aect coping behaviors among HIV + individuals (Folkman, Chesney, Pollack & Coates, 1993) raising the possibility of bidirectional in¯uences.…”
Section: Introductionmentioning
confidence: 99%
“…Les interviews étaient organisées autour d'une liste de questions, laquelle était conforme à la littérature portant sur les soignants et sur le deuil dans le contexte du VIH-sida (Folkman, Chesney, Collette, Boccellari & Cooke 1996;Folkman, Chesney, Cooke, Boccellari & Collette 1994;Folkman, Moskowitz, Ozer & Park 1997;Richards, Acree & Folkman 1999). Chaque interview commençait par une invitation à parler de la personne décédée et se poursuivait par des questions sur la façon dont la vie des soignants a été changée par l'expérience de soigner une personne et d'en faire le deuil.…”
Section: Protocole D'interviewunclassified
“…Une étude longitudinale effectuée à San Francisco et s'étalant sur une période de sept années (Folkman, Chesney, Collette, Boccellari, & Cooke 1996;Folkman & Moskowitz 2000;Folkman, Moskowitz, Ozer, & Park 1997;Moskowitz, Folkman, Collette, & Vittinghoff 1996;Wrubel & Folkman 1997) Les soignants dont le partenaire est mort pendant l'étude ont été interviewés subséquemment (Richards & Folkman 1997). La spiritualité a émergé comme un mécanisme important dans l'adaptation.…”
Section: Introductionunclassified
“…Certaines études identifient des aspects positifs quant à ce rôle dont une augmentation de l'estime de soi, de la fierté, un sentiment de gratification, le fait de se sentir proche de son partenaire ainsi qu'une meilleure communication avec ce dernier (Folkman, Chesney, Collette, Boccellari, & Cooke, 1996;Habermann, 2000;Kramer, 1997). Axelsson et Sjõden (1998) …”
unclassified